Associations between neighborhood, family factors and symptom change in childhood attention deficit hyperactivity disorder. (February 2021) - Sharp, Wendy; Mangalmurti, Aman; Hall, Carlisha; Choudhury, Saadia; Shaw, Philip
Abstract: Transactional theories view development as partly shaped by processes proximal to a child, which in turn interact with more distal neighborhood and societal contexts. Here we apply this theory to parse the interplay between neighborhood and familial factors on age-related change in symptoms of inattention and hyperactivity-impulsivity (ADHD). A cohort of 190 children (96 with ADHD) had a range of neighborhood and familial factors ascertained and had repeated clinical assessments over an average of 2.5 years at a U.S. research center. Using mixed model regression, we found an association between neighborhood wealth, but not the built environment, and the annual rate of change of inattentive but not hyperactive-impulsive symptoms. Following the transactional model, we asked if familial processes explain (mediate), modify (moderate), or act alongside this effect of neighborhood wealth on the change in a child's symptoms of inattention with age. We found evidence for moderation. Specifically, several family level variables – parental economic/education status and degree of family conflict and order moderated the effects of neighborhood wealth on the change in a child's inattentive symptoms. Children living in relatively affluent neighborhoods showed improvement with age in inattention, largely independent of variation in a wide range of familial factors. By contrast, children living in less affluent neighborhoods showed clinical deterioration only if the family had high levels of conflict or if the parents were of lower economic/educational status. Such work might help identify children whose familial and neighborhood contexts place them at risk of having ADHD symptoms persist or increase with age. Highlights: ADHD research has focused on child-level neurocognitive and genomic factors. We apply a transactional framework to incorporate familial and neighborhood processes. An association emerges between neighborhood wealth and childhood inattention. This association is moderated by familial wealth, degree of conflict, and order. Effects of living in poorer neighborhoods is 'buffered' by familial advantage.